2020
DOI: 10.1521/soco.2020.38.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Being Honest and Acting Consistently: Boundary Conditions of the Negativity Effect in the Attribution of Morality

Abstract: All the authors conceived the research idea. P. Rusconi conducted the literature review and drafted the first version of the article, while the other authors read and commented on it. We would like to thank John Skowronski and an anonymous reviewer for insightful comments and suggestions on the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 97 publications
(273 reference statements)
1
13
0
Order By: Relevance
“…These results support H1 and extend those about the established primacy of morality (e.g. Brambilla et al, 2021;Leach et al, 2015) and immorality (Rusconi et al, 2020) in social perception by approaching the gender and ethnicity intersection. They also confirm the relevance of considering both positive and negative moral qualities on social perception (Rusconi et al, 2020;Skowronski & Carlston, 1987).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results support H1 and extend those about the established primacy of morality (e.g. Brambilla et al, 2021;Leach et al, 2015) and immorality (Rusconi et al, 2020) in social perception by approaching the gender and ethnicity intersection. They also confirm the relevance of considering both positive and negative moral qualities on social perception (Rusconi et al, 2020;Skowronski & Carlston, 1987).…”
Section: Discussionsupporting
confidence: 84%
“…Brambilla et al, 2021;Leach et al, 2015) and immorality (Rusconi et al, 2020) in social perception by approaching the gender and ethnicity intersection. They also confirm the relevance of considering both positive and negative moral qualities on social perception (Rusconi et al, 2020;Skowronski & Carlston, 1987). Our study further shows that Moroccan men are the most devalued target on such a dimension, according to the outgroup male target hypothesis (Navarrete et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This is inconsistent with the intention conveyed by the component of competence (e.g., high creativity and high efficiency; Fiske et al, 2007 ); thus, high-intensity happy expressions might be facial cues for a lack of competence. In addition, target faces were found to be affected by a stronger positivity effect in the competence domain for moderate levels of behaviors ( Rusconi et al, 2020 ). Therefore, compared to high-intensity happy expressions, low-intensity happy expressions that are attributed to moderate levels of behaviors might work as to be facial cues for competence.…”
Section: Discussionmentioning
confidence: 99%
“…Behavior statements that are high in informativeness are diagnostic of a person’s true character, resulting in greater impression change [ 18 , 19 ]. Research has shown that the informativeness dimension is related to other dimensions: behavior statements that are morally negative are rated as more informative than morally positive statements [e.g., 20 , 21 ] and morally extreme behavior statements are rated as more informative than morally moderate statements [ 22 24 , see 25 for a review]. It has recently been established that the believability of behavioral information is also important to impression formation; person impressions are updated only when the information is considered to be believable, regardless of how informative or extreme the information is [ 5 ].…”
Section: Introductionmentioning
confidence: 99%